Natureza jurídica da denúncia anônima: liberdade de expressão ou direito de petição? - Giannella, Matteo Bassarani (2023)
The present work seeks to draw an overview of the institute of denunciation, in the administrative scope, giving special focus to its anonymous modality, seeking to demonstrate and elucidate how such an institute is received and processed by doctrine and jurisprudence in the field of control in Public Administration, especially in the face of the constitutional prohibition on anonymity. To this end, it is necessary to understand the characteristics that delineate the institute of denunciation and anonymous denunciation as instruments of popular participation directly derived from Fundamental Rights, in particular to what concerns the Right of Petition and Freedom of Speech. The delimitation of these Fundamental Rights is not merely discretionary, as we will see throughout our studies, and the identification of the constitutional grounds that enable the exercise of anonymous denunciation as a manifestation of these rights, as well as and essentially of their juridical nature, they are essential to the exercise of democracy and the pursuit of the principles of Public Administration, seeking to bring new light to the recurring debate as to the possibility of handling the anonymous complaint, that has not yet found a frontal and definitive institutional and legal shelter